2021
DOI: 10.1101/2021.01.14.426662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opioid withdrawal produces sex-specific effects on fentanyl-vs.-food choice and mesolimbic transcription

Abstract: BackgroundOpioid withdrawal is a key driver of opioid addiction and an obstacle to recovery. However, withdrawal effects on opioid reinforcement and mesolimbic neuroadaptation are understudied and the role of sex is largely unknown.MethodsMale (n=10) and female (n=9) rats responded under a fentanyl-vs.-food “choice” procedure during daily 2h sessions. In addition to the daily choice sessions, rats were provided extended access to fentanyl during 12h sessions. After two weeks of this self-administration regimen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 41 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…The heuristic framework of Heterologous Reinforcer Desensitization can be conceptualized as one particularly relevant manifestation of drug-induced “negative affect” proposed to be a driver of drug addiction ( Hogarth, 2020 ; Koob, 2021 ); however, Heterologous Reinforcer Desensitization suggests a subtly different research approach that focuses on drug vs. non-drug choice rather than on rates of drug self-administration in SODs. Indeed, the first drug self-administration study ever conducted in animals demonstrated a withdrawal-induced increase in opioid-vs.-food choice in morphine-dependent chimpanzees ( Spragg, 1940 ), and this phenomenon has been replicated in opioid-dependent baboons ( Griffiths et al, 1975 ), rhesus monkeys ( Negus, 2006 ; Negus and Rice, 2009 ), and rats ( Townsend et al, 2021 ) ( Fig. 1 D).…”
Section: Neuroscience With Choice Proceduresmentioning
confidence: 88%
See 1 more Smart Citation
“…The heuristic framework of Heterologous Reinforcer Desensitization can be conceptualized as one particularly relevant manifestation of drug-induced “negative affect” proposed to be a driver of drug addiction ( Hogarth, 2020 ; Koob, 2021 ); however, Heterologous Reinforcer Desensitization suggests a subtly different research approach that focuses on drug vs. non-drug choice rather than on rates of drug self-administration in SODs. Indeed, the first drug self-administration study ever conducted in animals demonstrated a withdrawal-induced increase in opioid-vs.-food choice in morphine-dependent chimpanzees ( Spragg, 1940 ), and this phenomenon has been replicated in opioid-dependent baboons ( Griffiths et al, 1975 ), rhesus monkeys ( Negus, 2006 ; Negus and Rice, 2009 ), and rats ( Townsend et al, 2021 ) ( Fig. 1 D).…”
Section: Neuroscience With Choice Proceduresmentioning
confidence: 88%
“…Rats were trained to choose between fentanyl and 18% Ensure, then rendered opioid dependent by introducing daily sessions of extended fentanyl access and withdrawal. After two weeks, there was an increase in fentanyl choice and a decrease in 18% Ensure choice ( Townsend et al, 2021 ). …”
Section: Neuroscience With Choice Proceduresmentioning
confidence: 99%
“…Numerous studies have identified molecular changes in the NAc that arise during opioid abstinence, or as a consequence of opioid use (Cahill et al, 2018; Ferguson et al, 2013; Lefevre et al, 2020; Martin et al, 2019; Mayberry et al, 2022; Spijker et al, 2004; Sun et al, 2016; Townsend et al, 2021), including recent work in postmortem human brain (Seney et al, 2021). Some notable similarities arise between our findings, and those of recent publications: neuronal morphology related genes are downregulated across species and paradigm (Lefevre et al, 2020; Mayberry et al, 2022; Townsend et al, 2021). Like our work in abstinent mice, Mayberry et al found downregulated Green Module genes in the NAc of male morphine self-administering rats (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus accumbens (NAc) is a key locus in brain reward-circuitry that undergoes distinct molecular, cellular, and structural changes during opioid abstinence. Opioid withdrawal reduces dopamine release in the NAc (Acquas et al, 1991; Fox et al, 2017; Pothos et al, 1991; Rossetti et al, 1992) and induces numerous transcriptional changes dependent on opioid, sex, and abstinence duration (Cahill et al, 2018; Ferguson et al, 2013; Hofford et al, 2021; Martin et al, 2019; Mayberry et al, 2022; Spijker et al, 2004; Sun et al, 2016; Townsend et al, 2021). Opioid cessation also causes morphological and electrophysiological changes to NAc neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we compared the 2 NAc studies (Seney et al [29], Townsend et al [28]) for which full genome-wide results were available. While both included males and females, only Townsend et al reported sex-specific results.…”
Section: Threshold-free Genome-wide Comparisonmentioning
confidence: 99%